Cardiac remodeling in ambitious endurance-trained amateur athletes older than 50 years. (25th November 2020) - Dalos, D; Dachs, T; Gatterer, C; Schneider, M; Binder, T; Bonderman, D; Hengstenberg, C; Panzer, S; Aschauer, S
Abstract: Background: Data on cardiac remodeling in athletes are conflicting and rarely available in veteran athletes. Purpose: Therefore, in this study we aimed to define echocardiographic features of healthy endurance athletes older than 50 years. Methods: We included probands aged >50 years, who have performed endurance sports at 70% of their maximum heart rate for at least 1 hour 3 times per week over the previous 5 years. Results: Between November 2018 and May 2019, 69 probands were recruited. Median age was 57 years (IQR 52–64) and 26% were female. Groups were formed according to the median training time of 6 hours per week: (A) 45 probands with ≥6 hours (IQR 6–10) and (B) 24 probands with <6 hours (IQR 3.5–5). Age, sex and body mass index were similar. Group A demonstrated slightly smaller right atrial and left atrial (LA) diameters when compared to probands in B (53mm (IQR 49–55) vs. 53mm (IQR 51–58), p=0.045, and 52mm (IQR 49–55) vs. 53mm (IQR 52–58), p=0.039, respectively) and showed preserved diastolic function (p=0.026) with lower E/E' ratio (7 (IQR 6–9) vs. 9 (IQR 7–10), p=0.039). Interventricular septal thickness and relative wall thickness ratio were similar. Global right and left ventricular (LV) strain were similar, but LA reservoir strain was higher in group A than in B (27% (IQR 22–34) vs. 20% (IQR 15–29), p=0.016). Conclusion: Endurance training in healthy athletes older than 50 years does not result in relevant chamber dilatation or LV hypertrophy and a weekly training duration of ≥6 hours seems beneficial to preserve diastolic function associated with an increased LA reservoir function. Funding Acknowledgement: Type of funding source: None